Escape from the cryptic species trap: lichen evolution on both sides of a cyanobacterial acquisition event. Issue 14 (11th May 2016) - Schneider, Kevin; Resl, Philipp; Spribille, Toby
Abstract: Large, architecturally complex lichen symbioses arose only a few times in evolution, increasing thallus size by orders of magnitude over those from which they evolved. The innovations that enabled symbiotic assemblages to acquire and maintain large sizes are unknown. We mapped morphometric data against an eight‐locus fungal phylogeny across one of the best‐sampled thallus size transition events, the origins of the Placopsis lichen symbiosis, and used a phylogenetic comparative framework to explore the role of nitrogen‐fixing cyanobacteria in size differences. Thallus thickness increased by >150% and fruiting body core volume increased ninefold on average after acquisition of cyanobacteria. Volume of cyanobacteria‐containing structures (cephalodia), once acquired, correlates with thallus thickness in both phylogenetic generalized least squares and phylogenetic generalized linear mixed‐effects analyses. Our results suggest that the availability of nitrogen is an important factor in the formation of large thalli. Cyanobacterial symbiosis appears to have enabled lichens to overcome size constraints in oligotrophic environments such as acidic, rain‐washed rock surfaces. In the case of the Placopsis fungal symbiont, this has led to an adaptive radiation of more than 60 recognized species from related crustose members of the genus Trapelia . Our data suggest that precyanobacterial symbiotic lineages were constrained to forming a narrow range of phenotypes, so‐called cryptic species, leading systematists until now to recognize only six of the 13 species clusters we identified in Trapelia . Abstract : See also the Perspective by Scheidegger